Cyclic Carbopalladation. A Versatile Synthetic Methodology for the Construction of Cyclic Organic Compounds - Negishi, Ei-ichi; Copéret, Christophe; Ma, Shengming; Liou, Show-Yee; Liu, Fang (Chemical reviews, 1996)
A new and versatile cyclization methodology based on cyclic carbopalladation is discussed. The carbopalladation-based cyclization methodology should prove to be one of the most general, versatile and selective.